2015
DOI: 10.1108/ijge-05-2013-0046
|View full text |Cite
|
Sign up to set email alerts
|

Business advisory services and risk among start-ups and young companies: a gender perspective

Abstract: This study aims to investigate the demand for business advisory services by owners of start-ups and young companies by taking a gender perspecitve. The study also examines whether risk-taking is more characteristic of masculine than feminine behaviour in this context. Design/methodA literature review examines business advisory services and risk aversion from a gender perspective. The empirical data are derived from interviews with owners of more than 2700 start-ups and young companies in Sweden. A number of ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…This leads female entrepreneurs to raise smaller amounts of capital compared to men (Coleman & Kariv, 2014;Kremel & Yazdanfar, 2015). Nevertheless, although Bardasi, Sabarwal, and Terrell (2011) found that female entrepreneurs receive smaller loans than their male counterparts, they found no evidence of gender discrimination in access to financing, nor did Fabowale, Orser, and Riding (1995) and Riding and Swift (1990) when looking into denial rates of loans and lines of credit.…”
Section: Literature Background Gender Differences In Financial Decisimentioning
confidence: 82%
See 1 more Smart Citation
“…This leads female entrepreneurs to raise smaller amounts of capital compared to men (Coleman & Kariv, 2014;Kremel & Yazdanfar, 2015). Nevertheless, although Bardasi, Sabarwal, and Terrell (2011) found that female entrepreneurs receive smaller loans than their male counterparts, they found no evidence of gender discrimination in access to financing, nor did Fabowale, Orser, and Riding (1995) and Riding and Swift (1990) when looking into denial rates of loans and lines of credit.…”
Section: Literature Background Gender Differences In Financial Decisimentioning
confidence: 82%
“…Recent studies have demonstrated that gender causes more difficulties when female entrepreneurs seek financing compared to male entrepreneurs (Brana, 2013;Burke, van Stel, Hartog, & Ichou, 2014;Gicheva & Link, 2013;Saparito, Elam, & Brush, 2013). This leads female entrepreneurs to raise smaller amounts of capital compared to men (Coleman & Kariv, 2014;Kremel & Yazdanfar, 2015). Nevertheless, although Bardasi, Sabarwal, and Terrell (2011) found that female entrepreneurs receive smaller loans than their male counterparts, they found no evidence of gender discrimination in access to financing, nor did Fabowale, Orser, and Riding (1995) and Riding and Swift (1990) when looking into denial rates of loans and lines of credit.…”
Section: Gender Differences In Financial Decision Makingmentioning
confidence: 99%
“…Several studies suggest that the credit requirements imposed by banks are more likely to favor male rather than female-led firms, mainly because lenders have different perceptions about the entrepreneurs' potential (Alsos & Ljunggren, 2017;Carter et al, 2007;Marlow & Patton, 2005). Compared to male-led enterprises, female-led firms may indeed face a higher rate of rejection of their loan applications (Cavalluzzo et al, 2002), partial rejection by the lender (Kremel & Yazdanfar, 2015;Treichel-Zimmerman & Scott, 2006), higher price conditions, or be required to provide higher collateral for the credit supplied (Alesina et al, 2013;Bellucci et al, 2010;Mascia & Rossi, 2017;Muravyev et al, 2009;Wu & Chua, 2012). It is worth noting, however, that this evidence is far from conclusive.…”
Section: Supply-side Predictionsmentioning
confidence: 99%
“…With regard to the supply side, on the other hand, a typical issue that female-led firms may face, compared to male-led enterprises, is a higher rate of rejection of their loan applications (see, for example, Cavalluzzo, Cavalluzzo, & Wolken, 2002). Additionally, women-led businesses may experience a partial rejection from the lender (Kremel & Yazdanfar, 2015;Treichel-Zimmerman & Scott, 2006), or may even face higher price conditions or be required to provide higher collateral than men in order to obtain credit (Alesina et al, 2013;Bellucci, Borisov, & Zazzaro, 2010;Mascia & Rossi, 2017;Muravyev, Talavera, & Schäfer, 2009;Wu & Chua, 2012). It is also worth mentioning that the literature on this issue is not conclusive and that several studies have not detected signs of gender-based discrimination (see, for example, Carter et al, 2007;Moro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The attributes associated with entrepreneurs may thus feel unattainable for some women, who tend to be the primary carers of children. While Lee-Gosselin and Grisé (1990) claim that self-employed women are already innovators: the choice to run their own business is atypical, with both personal and psychological risks; Kremel and Yazdanfar's (2015) exploration of the gendered dimensions of risk found that women were more likely to seek support to help mitigate perceived risks. However, the characterisation of risk-taking as a fundamental part of enterprise may not even be accurate: Greene and Storey's (2005) longitudinal survey found that those who were averse or neutral to risk were actually more likely to stay in business.…”
Section: Enterprise and Gendermentioning
confidence: 99%